Combined Surgical Approach for Obstructive Sleep Apnea Patient - Mahmoud A. K. Ebrahim; Osamah AlSanea; Abdulmohsen E. Al-Terki (Case Reports in Otolaryngology)
Obstructive sleep apnea (OSA) is a disease that is associated with high morbidity and mortality and can significantly impact the quality of life in a patient. OSA is strongly associated with obesity, and literature showed that weight loss will lead to improvement in OSA. The gold standard treatment for OSA is continuous positive airway pressure (CPAP). However, other methods of treatment are available. One of these methods is multilevel sleep surgery (MLS). Literature showed that bariatric surgery can also improve OSA. A common question is which surgical procedure of these two should be performed first. We present a 5-year follow-up of a patient who underwent simultaneously bariatric surgery and MLS. His apnea-hypopnea index (AHI) decreased from 53 episodes per hour to 5.2 per hour within the first 18 months, which was measured via a level 3 polysomnography. Five years after the surgery, a repeat level 3 polysomnography showed an AHI of 6.8 episodes per hour, and the patient is asymptomatic. The patient maintained his weight and did not use CPAP after the combined surgery during the five-year period.